Motif utama guru melanjutkan pelajaran dan tahap motivasi terhadap program pengajian - Muhamad, Mazanah; Mat Junoh, Adanan (Universiti Putra Malaysia Press, 2004)
The study sought to identify teachers' primary motives for pursuing education through a distance learning programme at the Institute for Distance Education and Learning (IDEAL) Universiti Putra Malaysia, and to determine their motivation level towards that programme. A sample of 360 teachers from four IDEAL learning centers was randomly selected for the purpose. Data was collected by using a survey instrument specifically developed for the study by drawing upon Boshier's (1973) Educational Participation Scale. A total of 272 completed questionnaires was analyzed by using the SPSS programme. The study identified seven primary motives for teachers pursuing higher education namely (i) professional advancement; (ii) cognitive interest; (iii) social welfare; (iv) personal goal; (v) learning activities; (vi) external expectation, and (vii) social relationship. The teachers reported high motivation level towards the learning programme. There is significant difference in motivation level among teachers of different race, semester, programme of study and school location.